Developmental trajectories of balance performance in preschoolers: age and gender differences for 3–6 years old Chinese children - Li, Ruiyuan; Zhu, Jiefeng; Li, Ruiqin; Wang, Xiaoting; Tian, Taishan; Wan, Bingjun (Frontiers in Physiology, 2025)
ObjectivesPreschool age is a critical stage of postural balance development. Compromised stability may impede a child’s ability to acquire basic motor skills and, in turn, the capacity to participate in physical activities. However, little information exists on balance in preschool years, few studies have comprehensively evaluated all four balance types. in preschool children. Therefore, the purpose of the present study was to assess balance development in a multidimensional way in preschool children and to examine the effect of age and gender on preschool children’s balance performance.MethodsA total of 619 children (296 boys and 323 girls; aged 3–6 years) from China participated in the present study. Static steady-state, dynamic steady-state, proactive, and reactive balance performance were assessed using the one-leg stand test (OST), 10-meter walk test (10-MWT), functional reach test (FRT), and push and release test (PRT), respectively. Two-way analysis of variance was used to evaluate differences between age and gender groups.ResultsThe results revealed significant differences in gender for OST (η2p = 0.037, p < 0.001), 10-MWT (η2p = 0.012, p = 0.007), and FRT (η2p = 0.016, p = 0.002). Age positively affected all balance tests, as the OST (η2p = 0.336, p < 0.001), 10-MWT (η2p = 0.448, p < 0.001), FRT (η2p = 0.392, p < 0.001), and PRT (η2p = 0.045, p < 0.001). Older preschool children performed better than their younger counterparts in all the tests. No significant interactions between age groups and gender were found.ConclusionThis study provided age- and gender-specific balance performance data in Chinese preschool children. All various balance types increased with age in this cohort. Static steady-state, dynamic steady-state, and proactive balance develop faster compared to reactive balance. Gender differences in balance already exist at the preschool age. These findings can assist health, physical education, and school professionals in assessing and improving balance in preschoolers using multiple indicators for different types of balance and designing age and gender-appropriate balance tasks.